Myxomycete diversity in Costa Rica - Rojas Alvarado, Carlos Alonso (2018)
An updated analysis of myxomycete diversity in Costa Rica is provided herein as a product of an extensive data mining-based study intended to normalize the information on myxomycetes from that country. Within the context of the Mesoamerican Biodiversity Hotspot, the 242 species of myxomycetes are reported herein demonstrated the potential of this area for diversity-based studies. For the construction of the updated species list, a thorough analysis that included examination of vouchers and a literature review has been carried out, and some species previously included in other works have been rejected due to inconsistencies or misidentification. The present contribution is essential to address the Wallacean shortfall within Mesoamerica and important for providing updated data on microorganisms in the context of regional biodiversity monitoring